Different types of N nutrition and their impact on endogenous cytokinin levels in Festulolium and Trifolium pratense - M. Neuberg; D. Pavlíková; E. Žižková; V. Motyka; M. Pavlík (Plant, Soil and Environment, 2011)
This study aims to reveal and to compare effects of two different systems of nitrogen (N) nutrition (sidedress application or injection application) on toxicity of NH4+ and mixed nutrition. We investigated whether NH4+ or mixed (NH4NO3) application causes significant changes in the endogenous levels of cytokinins (CK), whole plant N and their effects on yield of selected plants. Ammonium sulphate or ammonium nitrate were used as N source in the pot experiment. The yield of Festulolium and Trifolium pratense L. above-ground biomass and roots was more substantially enhanced after sidedress application of both ammonium sources in comparison with injection application. Our results confirmed that the accumulation of CKs in plants is in correlation with their N content (R2 = 0.66-0.98). Proportions between individual CK forms remained relatively steady and their dynamics exhibited similar trends after N application. Our results indicate that the negative effect of the application of NH4+ on the growth of Festulolium and clover plants could be effectively modulated by the presence of NO3-.